2019
DOI: 10.1093/heapol/czz017
|View full text |Cite
|
Sign up to set email alerts
|

‘Doing more with less’: a qualitative investigation of perceptions of South African health service managers on implementation of health innovations

Abstract: Building resilience in health systems is an imperative for low- and middle- income countries. Health service managers’ ability to implement health innovations may be a key aspect of resilience in primary healthcare facilities, promoting adaptability and functionality. This study investigated health service managers’ perceptions and experiences of adopting health innovations. We aimed to identify perceptions of constraints to adoption and emergent behaviours in response to these constraints. A convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 48 publications
2
41
0
3
Order By: Relevance
“…Limited understanding of the importance of mental health counselling by other facility staff and the lack of resources (confidential space and time) required to provide adequate care as key implementation barriers to address during counselling scale up. Prior studies have also identified these as potential barriers to the implementation of mental health counselling in PHC facilities (Brooke-Sumner et al 2019;Myers et al 2019a, b). Strong leadership from facility managers can help staff navigate many of the resource challenges to counselling implementation (Brooke-Sumner et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Limited understanding of the importance of mental health counselling by other facility staff and the lack of resources (confidential space and time) required to provide adequate care as key implementation barriers to address during counselling scale up. Prior studies have also identified these as potential barriers to the implementation of mental health counselling in PHC facilities (Brooke-Sumner et al 2019;Myers et al 2019a, b). Strong leadership from facility managers can help staff navigate many of the resource challenges to counselling implementation (Brooke-Sumner et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Employee involvement has been positively associated with a large number of significant changes in quality care improvements and chronic illness management as engaged employees collaborate, perform at a higher level and are innovative [9,38]. A qualitative study on constraints for adopting health innovations into practice indicated that the hierarchical culture of the South African health system does not support innovation and creating change at facility level [39]. Creating change cultural index also obtained a low score in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Creating change cultural index also obtained a low score in this study. Decisions on what new innovative interventions to be introduced are usually concluded at higher (district and provincial) management level with very little bottom-up communication or consultation [39]. Adaptability cultural trait is a critical strength in an organization that's undergoing a transformation [11], and this trait would need to be fortified in these PHC clinics as part of the primary healthcare reengineering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of trained counsellors who were not their usual HIV care providers seemed to enhance the acceptability of screening and the brief alcohol reduction intervention. Professional counsellors are, however, absent from the current public health workforce, largely due to the country's chronic shortage of financial and human resources for mental health [32,33]. Implementing screening and brief alcohol reduction interventions on scale, therefore, will require alternative delivery agents.…”
Section: Discussionmentioning
confidence: 99%